Relationship between body mass index and binge eating disorders - Pereira, Filomena (2017)
Periodic Eating Compulsion (PEC) is most frequently associated to obese and overweight subjects. However, studies indicate that subjects with a normal weight also show PEC episodes. Methods: A quantitative exploratory study was designed with the purpose to know the ratio between Body Mass Index (BMI) and PEC, involving a sample of 306 people of both genders with different BMI categories (0.3% of the sample was underweight, 21.9% had normal weight, 23.5% were pre-obese, 31.4% had Grade I obesity, 14.1% had Grade II obesity and 8.8% had Grade III obesity). Data was collected by means of the Periodic Eating Compulsion Scale (PCES) at 4 hospitais in the North and Centre regions of the country. Results: In the overall sample, 219 subjects (71. 6%) were found to have no PEC, 49 subjects (16. 0%) had moderate PEC and a further 38 subjects (12.4%) had severe PEC. In consonance with the literature in this field, the descriptive study of the study variables showed that all the BMI category groups - with the exception of a low weight patient - showed PEC behaviours. Conclusion: It was observed that the higher the BMI, the higher the number of subjects with compulsive-type PEC, a fact considered to be pertinent for new studies in this overweight population. The results show the need for nutritional education and renewed vigilance in the population with PEC.